Environmental relevant levels of the cytotoxic drug cyclophosphamide produce harmful effects in the polychaete Nereis diversicolor - Fonseca, T. G. [UNESP]; Auguste, M.; Ribeiro, F.; Cardoso, C.; Mestre, N. C.; Abessa, D. M.S. [UNESP]; Bebianno, M. J. (My University, 2018)
Cytotoxic drugs applied in chemotherapy enter the aquatic environment after patient's metabolism and excretion, in both main compounds and their respective metabolites. The increased consumption and discharge of these drugs raise concern on the genotoxic burden to non-target aquatic species, due to their unselective action on DNA. Settlement and adsorption of cytotoxic drugs to aquatic sediments pose risks to benthic species through chronic exposure. The aim of the present study was to assess the effects induced by the anticancer drug cyclophosphamide (CP) on the polychaete Nereis diversicolor, after 14 days of exposure to environmental relevant concentrations (10, 100, 500 and 1000 ng L−1). Burrowing impairment, neurotoxicity (Acetylcholinesterase - AChE activity), oxidative stress (superoxide dismutase – SOD; catalase – CAT; glutathione peroxidases - GPXs activities), biotransformation (glutathione-S-transferases - GST), oxidative damage (lipid peroxidation - LPO) and genotoxicity (DNA damage) were assessed. Burrowing impairments were higher at the lowest CP concentrations tested. The higher CP levels tested (500 and 1000 ng L−1) induced a significant inhibition on the enzymatic antioxidant system (SOD, GPx) and on GST activity. DNA damage was also significant at these concentrations as an outcome of CP metabolism, and high levels of oxidative damage occurred. The results showed that the prodrug CP was metabolically activated in the benthic biological model N. diversicolor. In addition to the potential cytotoxic impact likely to be caused in aquatic species with similar metabolism, N. diversicolor proved to be reliable and vulnerable to the cytotoxic mode of action of CP, even at the lower doses.
Keywords: Anticancer drugs; Cyclophosphamide; Genotoxicity; Oxidative stress; Polychaetes; Sediments